Extracción y cuantificación de isoflavonas totales expresados en genisteína en granos de glycine max l. (soya) provenientes de la provincia de Jaén - Cajamarca”. - Díaz Solano, Hugo Ricardo (2009)
This research was aimed to draw the Total Isoflavones and determine the concentration of Total Isoflavone expressed in genistein in dry matter of grains or seeds of Glycine max L. (Soya) from the province of Jaen, Cajamarca, harvested in September by UV-Visible spectrophotometric method described by Kostennikova Z. adapted by the Chair of Pharmacobotany and Pharmacognosy,of the Faculty of Pharmacy and Biochemistry of the UNT27. The Taxonomic Classification and Description of the species Glycine max L. (Soya) was held in the Herbarium Truxillense (HUT) of the Universidad National de Trujillo. Drying, grinding, degreasing and depigmentation of the drug, extraction and hydrolysis of glycosides of isoflavones, purification and UV-Visible spectrophotometric quantification was used to extract and quantify the total isoflavones. The concentration of Total Isoflavone expressed in Genistein was at 0.49661%, within the range of 0.2% to 0.7% (according to the Argentine Association of Dieticians and Nutritionist Dietitians) 33. Statistically, the arithmetic average and the Student t distribution, we used verifying the results of the solution problem found within its confidence interval and its coefficient of variability is located in the category of high representativeness Statistics